Homosexualités et tolérance sociale - Richard, Louis; Seguin, Marie-Thérèse; Groupe de recherche interuniversitaire et interdisciplinaire sur la gestion sociale (Éditions d'Acadie, 1988)
GRIIGES, Groupe de recherche interuniversitaire et interdisciplinaire sur la gestion sociale. Actes d'un colloque tenu du 9 au 11 oct. 1987 à l'Université de Moncton.
Section: 194 pages ; 23 cm
Keywords: 1900-1999; 1980-1989; LGBTQIA2+; amérique du nord; amériques; approches et analyses; canada; cours; discipline; homophobie; hétérosexisme; identités LGBTQIA2+; inégalités; justice sociale; nouveau-brunswick; premier cycle; périodes historiques; queer; régions géographiques; sexualité; shm4000; systèmes d'oppressions; thématiques

Can the Subaltern Speak? - Spivak, Gayatri Chakravorty (Marxism and the Interpretation of Culture, 1988)
Keywords: 1900-1999; 1980-1989; approches et analyses; cours; fem1000; histoire et politique; incontournable; inégalités; mondialisation; pol4022; premier cycle; périodes historiques; systèmes d'oppressions; thématiques; théories féministes; études postcoloniales

If women counted: A new feminist economics - Waring, Marilyn (Harper & Row, 1988)
This is a revolutionary and powerfully argued feminist analysis of modern economics, revealing how woman's housework, caring of the young, sick and the old is automatically excluded from value in economic theory. An example of this pervasive and powerful process is the United Nation System of National Accounts which is used for wars and determining balance of payments and loan requirements.
Keywords: OFDIG; approches et analyses; discipline; femmes*; inégalités; sciences de la gestion; systèmes d'oppressions; thématiques; travail; économie